Exploring socioeconomic concerns in Italian social media discourse on migration: A sentiment analysis of X posts - Indelicato Alessandro; Martín Juan Carlos; Di Rocco Rossella Maria Pia; Marinello Vincenzo (Psychology of Language and Communication, 2025)
Social media platforms, particularly Twitter (now X), have transformed into significant arenas for public debate on immigration, showcasing a diverse spectrum of opinions and emotions. The current study utilized sentiment analysis, a method widely used in social media research, to delve into public sentiment in social network comments related to immigration, specifically focusing on Italy. The study compiled a dataset of X posts containing the keyword “immigrati” (immigrants) and conducted sentiment analysis to gauge the prevailing attitudes. The study aimed to uncover prevailing themes and connections in public discourse by identifying the most frequent topics. These patterns shed light on the primary topics and terms associated with immigration in Italy and their interrelationships. The findings contribute to a deeper understanding of sentiment and discourse surrounding immigration on social media, particularly within the Italian context. Results revealed the intricate and multifaceted nature of public opinion on immigration, with Italian concerns predominantly revolving around the irregular status of newcomers, the role of NGOs, and economic and safety issues, reflecting the complex nature of public opinion on immigration in contemporary digital spaces.